Mixotrophy as a survival strategy in Antarctic lakes - Laybourn-Parry, J.; Roberts, E. C.; Bell, Elanor M. (2000)
Mixotrophy is a widespread phenomenon among planktonic protists. It involves the combination of autotrophy and heterotrophy in varying degrees. Many phytoflagellate species ingest bacteria as a means of obtaining nutrients for photosynthesis or for supplementing their carbon budget under light limitation. Ciliates either sequester the plastids of their algal prey or harbour endosymbiotic algae. In the saline lakes of the Vestfold Hills and in Lakes Hoare and Fryxell in the McMurdo Dry Valleys the dominant phytoflagellates ingest bacteria, and there is evidence to suggest that during the winter months they lack chlorophyll and may become entirely heterotrophic. In Lake Fryxell phagotrophic pyhtoflagellates (cryptophytes) made a significant impact on bacterial production, removing up to 13% of the bacterial biomass day-1. These cryptophytes suffered predation from Plagiocampa (a ciliate), which appears to harbour them for a significant period before digesting them. We suspect that this may be equivalent to an intermediate stage in the evolution of mixotrophy. A significant number of the planktonic ciliates in Antarctic lakes were mixotrophic. The final evolutionary end point is the situation seen in Mesodinium rubrum, which now relies entirely on its cryptophycean endosymbiont and no longer ingests food. Mesodinium is the dominant ciliate in many of the saline lakes of the Vestfold Hills, which are of marine origin. It can reach abundances in excess of 60,000l-1 in Ace Lake, This ciliate is a ubiquitous member of the marine plankton worldwide and has successfully adapted to the lacustrine environment in Antarctica. The evidence suggests that among the survival strategies seen in Antarctic lake plankton, mixotrophy plays and important role among a number of the dominant protozoan species.